THE EFFECT OF PROJECT-BASED LEARNING (PjBL) MODEL ON STUDENTS' LEARNING OUTCOMES IN SOCIAL ARITHMETIC MATERIALS IN GRADE VII OF SMP NEGERI 1 TOMPASOBARU - Liando, Natalia Kintania; Tumalun, Nicky Kurnia; Pitoy, Cory (Jurnal Pendidikan Matematika dan IPA, 2026)
The mismatch of learning models with student competencies has the potential to inhibit classroom interaction and reduce learning engagement. This impact is seen in the decline of academic achievement. An effective solution is the implementation of Project Based Learning (PjBL), a student-centred approach based on creative-innovative methods. This study examined the effect of PjBL on improving learning outcomes using a quantitative experimental design. The research subjects consisted of students of class VII A (experimental) and VIII B (control) at SMP Negeri 1 Tompaso Baru.. Based on the results of research using the t-test, obtained tcount= 3.605 and ttable value at a significant level α = 0.05 and df = 38 is 1.685, thentcount> ttable (3.605> 1.685). This shows that the Project Based Learning (PjBL) learning model is higher than the conventional learning model on student learning outcomes in social artimatics class VII SMP Negeri 1 Tompaso Baru.